Pengaruh stress ball therapy terhadap kecemasan pasien pre operasi sectio caesarea - Galih Adi Prasetyo; Anik Suwarni; Ni’mah Mufidah (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Sectio caesarea surgery is a surgical procedure that often causes anxiety in patients. This anxiety needs to be reduced to prevent adverse physical and psychological impacts. One potential non-pharmacological method is stress ball therapy, which can provide a relaxing effect and reduce anxiety through sensory stimulation. Purpose: To determine the effect of stress ball therapy on anxiety in pre-operative sectio caesarea patients at RSUD dr. Soehadi Prijonegoro Sragen. Method: This study used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of 35 mothers undergoing cesarean section who met the criteria. Stress ball therapy intervention was performed before entering the operating room. The participants held the ball for 3-5 seconds, repeating it 10 times within 1-minute, alternating hands. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. Results: Statistical analysis showed a difference in mean scores from 30.31 to 21.34, and a Marginal Homogeneity Test with a p-value of 0.000 (p < 0.05). This indicates that stress ball therapy has an effect on anxiety levels in pre-sectio caesarea patients. Conclusion: Stress ball therapy has been proven effective as a complementary therapy in reducing post-sectio caesarea pain. It can be used as a reference in nursing practice to improve care for pre-operative mothers.